2007
DOI: 10.1111/j.1600-0404.2006.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of length of stay for stroke patients

Abstract: Stroke severity is a strong and reliable predictor of LOS. The results of this study can be used as a baseline for evaluating cost-effectiveness of stroke care changes, e.g. organizational changes or evaluation of new drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 18 publications
4
83
2
2
Order By: Relevance
“…4 A total NIHSS >25 is an exclusion criterion for rt-PA. 13 One small study looked at the NIHSS items and found that increases in the loss of consciousness and motor limbs total scores were related to neurological deterioration within the first 120 minutes after administration of intravenous rt-PA. 14 Another study reported that an improvement in the total NHISS of >3 points at 15 minutes or of >5 points at 30 minutes predicts a more favorable outcome and helps identify patients who are not responding to rt-PA. 15 A Swedish study of 347 patients found that for each point on the baseline NIHSS there was an increase in length of stay by 0.8 days and the total length of stay (including rehabilitation) by 3.4 days up to a NIHSS of 19 points. 16 The NIHSS was better at predicting the presence of dysphagia compared with a nursing dysphagia screening tool in a retrospective cohort study of veterans admitted with ischemic stroke. 17 Several studies have looked at outcome after hospitalization.…”
Section: Validitymentioning
confidence: 99%
“…4 A total NIHSS >25 is an exclusion criterion for rt-PA. 13 One small study looked at the NIHSS items and found that increases in the loss of consciousness and motor limbs total scores were related to neurological deterioration within the first 120 minutes after administration of intravenous rt-PA. 14 Another study reported that an improvement in the total NHISS of >3 points at 15 minutes or of >5 points at 30 minutes predicts a more favorable outcome and helps identify patients who are not responding to rt-PA. 15 A Swedish study of 347 patients found that for each point on the baseline NIHSS there was an increase in length of stay by 0.8 days and the total length of stay (including rehabilitation) by 3.4 days up to a NIHSS of 19 points. 16 The NIHSS was better at predicting the presence of dysphagia compared with a nursing dysphagia screening tool in a retrospective cohort study of veterans admitted with ischemic stroke. 17 Several studies have looked at outcome after hospitalization.…”
Section: Validitymentioning
confidence: 99%
“…This selection may result in the exclusion of individuals with less severe stroke, fewer complications or comorbidities, expedited discharge, or early mortality. 14 The frequency of feeding tube use was compared among hospitals with a minimum of 30 annual stroke admissions. 15 This minimum admission volume ensures that 95% confidence intervals (CIs) were no wider than 10% for hospitals using feeding tubes at the mean rate (approximately 8%).…”
mentioning
confidence: 99%
“…These patients often need a longer stay in hospital. 56 Dementia before a stroke increases the risk for both early death 27 and death within 1 year, 8 and also increases the risk of a recurrent stroke. 8 Most likely, the explanation is multifactorial.…”
Section: Prognosismentioning
confidence: 99%